Dietary Strategies for Better Immune Function: Evaluating the Role of Diet in Immune Function - Talat, Amna; Mohsin, Areej; Zafar, Khadija; Momna; Wahla, Muhammad Rizwan; Haris, Maria; Sajid, Mahpara (Indus Journal of Bioscience Research, 2025)
It is commonly known that inadequate nutrition can affect immunological function. Increased consumption of several nutrients over the currently advised levels may assist optimize immunological activities, such as enhancing defence function and, consequently, infection resistance, while preserving tolerance, according to mounting data. Nutrition serves a vital part in maintaining immune function, shaping the possibility to infections, autoimmune diseases, and chronic conditions. This review thoroughly analyzes nutritional plans and their effect on defense efficiency, merging evidence from clinical, biochemical and epidemiological studies. It explores how malnutrition damage defense response and interfere with gut barrier stability and modify microbiota formation. Specific reinforcement is on vital micronutrients including Vitamin A, C, D, E, B6, B12, folate, iron, zinc, selenium, and copper, and their functional part in aiding innate and adaptive response. It also analyzes the gut-immune axis and the part of probiotics and prebiotics in improving mucosal defense by microbial maintenance. Dietary epigenetics are examined in the setting of maternal and infant life nutrition, evaluating how availability of adequate nutrients during first 2 years of life can outline defense mechanism and prolonged well-being. Recent findings on nutritional polyphenols, bioactive peptides and omega-3 FAs are analyzed, specifically about capacity in reducing inflammation and autoimmunity. Nutritional strategies for immunocompromised communities, like old age people or persons with chronic diseases are also analyzed.